The effect of ground vegetation management on competition between the ants Oecophylla longinoda and Pheidole megacephala and implications for conservation biological control - Seguni, Z.S.K.; Way, M.J.; Mele, P. van (Elsevier, 2011)
In tropical Africa and Asia, two species of the predatory ant genus, Oecophylla, play a crucial role in protecting tree crops against pests and enhancing the quality of fruits and nuts. As predatory effectiveness is influenced by the presence of other dominant ant species, understanding the ecological factors at work in agroecosystems lies at the basis of conservation biological control. Over three and a half years, the effect of ground vegetation management on the beneficial tree-nesting ant Oecophylla longinoda (Latreille) and its competitor, the ground-nesting ant, Pheidole megacephala (Fabricius), was studied in a citrus orchard in Tanzania. When ground vegetation was present, P. megacephala tolerated O. longinoda and to some extent cohabited with this ant in citrus trees. However, after clean cultivation, P. megacephala displaced O. longinoda from tree crowns and became the sole occupant of the majority of trees. Displacement could be reversed by reversing the weed management regime, but this took time. Two years after the establishment of ground vegetation about half of the trees were colonized by Oecophylla only. Maintaining ground vegetation in tree crop plantations benefits the establishment and abundance of Oecophylla over Pheidole and is recommended in order to improve the efficiency of biological control of tree pests. The use of Amdro ant bait (hydramethylnon) to control P. megacephala is discussed. Boosting agroecological innovations, such as the one described in this paper, could benefit smallholder producers